Discovery of the Regularity of Acupuncture Point Selection Prescription for Lumbar Disc Herniation based on Data Mining - Zhang, Jing (Journal of Contemporary Medical Practice, 2025)
This study aimed to explore the acupoint selection, combination patterns, and optimal core acupoint groups in acupuncture treatment for lumbar disc herniation (LDH) based on data mining of modern domestic and international randomized controlled trials (RCTs). Computerized searches were conducted in multiple databases, including VIP, CNKI, WF, SCI, and PubMed, for literature published between 2014 and April 30, 2024. A total of 808 articles involving 155 acupoints were analyzed using Excel, Jadad scale scoring, IBM SPSS Statistics 26, and RStudio 4.4.1. Results showed that electroacupuncture had the highest efficacy (92.37%). The top three high-frequency acupoints were Weizhong (BL40), Huantiao (GB30), and Shenshu (BL23). The most frequently used meridians were the Bladder Meridian of Foot-Taiyang, Gallbladder Meridian of Foot-Shaoyang, and Governor Vessel. The acupoint pair “Weizhong (BL40) → Huantiao (GB30)” had the highest support (57.18%) and confidence (83.24%) in association rule analysis. In conclusion, electroacupuncture is the most effective method for LDH treatment. The high-frequency acupoints and meridians identified in this study provide valuable guidance for clinical acupoint selection and combination in acupuncture therapy for LDH.